An Interface Pullout Formula for Extensible Sheet Reinforcement. Issue 5 (1996) - Sobhi, S.; Wu, J.T.H.
Abstract : Pullout tests have been widely used to evaluate soil reinforcement interface properties for the design and analysis of reinforced soil structures. However, there are difficulties interpreting pullout test results particularly when extensible materials, such as geotextiles, are used as reinforcement. In this study, an analytical model (an "interface pullout formula") is presented for predicting and interpreting pullout test results in a unified and consistent manner. The model is based on three postulates that were deduced from the measured behavior of laboratory pullout tests and numerical results from finite element analyses. A number of applications of the interface pullout formula for predicting and interpreting the results of pullout tests are presented, including: how to predict the active length at a given applied pullout force; how to predict the pullout failure force for reinforcement of a given length; how to determine the coefficient of friction from results of a pullout test; and, how to predict the displacement at any point along the reinforcement for a given applied pullout force. Results using the interface pullout formula are shown to be in good agreement with the results of an instrumented pullout test and finite element analyses.